2019
DOI: 10.1111/hiv.12785
|View full text |Cite
|
Sign up to set email alerts
|

Significant chronic airway abnormalities in never‐smoking HIV‐infected patients

Abstract: Objectives The aim of the study was to describe chronic lung disease in HIV‐infected never‐smokers by looking at clinical, structural and functional abnormalities. Methods This comparative cross‐sectional study included 159 HIV‐infected never‐smoking patients [mean (± standard deviation) age 54.6 ± 9.1 years; 13.2% female; 98.1% with undetectable viral load] and 75 nonmatched never‐smoking controls [mean (± standard deviation) age 52.6 ± 6.9 years; 46.7% female]. We examined calcium scoring computer tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
(55 reference statements)
0
16
0
1
Order By: Relevance
“…7,19 However, CT imaging studies evaluating never-smokers or adolescents with HIV have shown that both airway disease in general as well as small airway disease specifically were more frequently observed in HIV-positive participants compared with controls. [19][20][21] Importantly, these studies have been crosssectional in design and reflect not only recent and ongoing HIV-related damage, but also historical tissue damage. This historical damage includes insults from previous HIV-associated pulmonary infections, lengthy exposure to HIV viraemia, and the cumulative exposures to inhaled toxic substances, such as those from smoking.…”
Section: Discussionmentioning
confidence: 99%
“…7,19 However, CT imaging studies evaluating never-smokers or adolescents with HIV have shown that both airway disease in general as well as small airway disease specifically were more frequently observed in HIV-positive participants compared with controls. [19][20][21] Importantly, these studies have been crosssectional in design and reflect not only recent and ongoing HIV-related damage, but also historical tissue damage. This historical damage includes insults from previous HIV-associated pulmonary infections, lengthy exposure to HIV viraemia, and the cumulative exposures to inhaled toxic substances, such as those from smoking.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is noteworthy that emphysema originates around the small airways and that never-smoking PLWH have been found to have small airway dysfunction (32). Moreover, a recent study that included 159 never-smoking PLWH on cART and 75 neversmoking uninfected controls, found a 4-fold increased risk of CT signs of emphysema in PLWH compared to uninfected controls (7). Taken together, these findings suggest that HIV itself, possibly through upregulation of IL-1b dependent inflammatory pathways, could cause destruction of lung parenchyma compatible with emphysematous changes.…”
Section: Discussionmentioning
confidence: 99%
“…During the current combination antiretroviral therapy (cART) era, comorbidities such as chronic pulmonary diseases are more prevalent in people living with HIV (PLWH) than in the background population (1)(2)(3). Emphysema, characterized by enlargement of terminal air sacs and destruction of alveolar walls, has been suggested to occur more frequently and at younger age in PLWH than in uninfected controls (4)(5)(6)(7). We previously studied radiographic emphysema in PLWH, and although we did not find HIV to be independently associated with emphysema, we found respiratory symptoms to be more prevalent in PLWH with emphysema compared to controls, suggesting a greater clinical impact of emphysema in this population (8).…”
Section: Introductionmentioning
confidence: 99%
“…Four of the studies were from an outpatient clinic in Italy, the Modena HIV metabolic clinic (21)(22)(23)(24). The enrolled participants had >18 months of cART exposure (cART coverage 100%) and were >18 years old.…”
Section: The Modena Human Immunodeficiency Virus Metabolic Clinicmentioning
confidence: 99%